Decreased level of serum NT-proCNP associates with disease severity in COVID-19 - Bojti, Istvan; Przewosnik, Anne-Sophie; Luxenburger, Hendrik; Hofmann, Maike; Neumann-Haefelin, Christoph; Eßer, Jennifer; Siegel, Patrick Malcolm; Maier, Alexander Andreas; Bojtiné Kovács, Sarolta; Kardos, Laszlo; Csanádi, Zoltan; Rieder, Marina; et al. (Respiratory research, 2023)
C-type natriuretic peptide (CNP) is an endothelium-derived paracrine molecule with an important role in vascular homeostasis. In septic patients, the serum level of the amino-terminal propeptide of CNP (NT-proCNP) shows a strong positive correlation with inflammatory biomarkers and, if elevated, correlates with disease severity and indicates a poor outcome. It is not yet known whether NT-proCNP also correlates with the clinical outcome of patients suffering from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. In the current study, we aimed to determine possible changes in the NT-proCNP levels of patients with coronavirus disease 2019 (COVID-19), with special regard to disease severity and outcome.